Microwave Absorption Properties of Fe3O4/Graphene Oxide Nanocomposites Synthesized from Coconut Shell Waste - Syahputra , Ilham; Darvina, Yenni; Ratnawulan, Ratnawulan; Hidayat, Rahmat (Journal of Experimental and Applied Physics, 2024)
Electromagnetic wave absorption technology is one of the technologies that need to be developed to control the problems caused by Electromagnetic Interference (EMI). This technology has created a material called Radar Absorbing Material (RAM) that Making RAM can be formed with material modifications such as nanocomposite materials. The manufacture of Fe3O4 nanocomposites and Graphene Oxide (GO) synthesized from coconut shell waste is one of the studies that need to be studied and developed at this time. Variations in the composition of Fe3O4 and GO used can determine the ability of microwave absorption. This study aims to analyze the microwave absorbing properties of Fe3O4/GO nanocomposites from coconut shell waste. The materials used to make this nanocomposite are magnetite (Fe3O4) and GO synthesized from coconut shell waste. This research uses experimental methods, with variations in the composition ratio between Fe3O4 and GO, namely 20% Fe3O4: 80% GO, 30% Fe3O4: 70% GO, and 40% Fe3O4: 60% GO. Characterization was carried out using a Vector Network Analyzer (VNA) to determine the nature of microwave absorption. The VNA characterization results found the influence of variations between Fe3O4 and GO composites. Based on the research results, the lowest absorption coefficient percentage was 95.50% at a frequency of 8.38 GHz for the composition variation of 20% Fe3O4 and 80% GO. The highest absorption coefficient was 96.43% at a frequency of 8.42 GHz for the composition of 40% Fe3O4 and 60% GO. The addition of Fe3O4 can make the absorption value of the material to microwaves higher.